Model Pembelajaran Problem Based Learning (PBL): Efeknya Terhadap Pemahaman Konsep dan Berpikir Kritis - Yulianti, Eka; Gunawan, Indra (Indonesian Journal of Science and Mathematics Education, 2019)
Abstract: This study aims to investigate the effectiveness of the learning problem based learning (PBL) model  against understanding of concepts and critical thingking of students on senior high school temperature and heat material. Subjects in this study were students class X SMA N 1 waway karya lampung timur amounted to 70 student. The method used is a quasi experimental design with pretets-posttest control design. Data understanding of concepts and critical thingking were collected by instruments test essay questions. The obtained data then analyzed by using multivariate (MANOVA) test. The results of the analysis  with spss 17.00 program show that there is a significant effect in applying the guided of the learning problem based learning (PBL) model against understanding of concepts and critical thingkingof students. The gain score of understanding of concepts in experimental class was 0,51and and the gain score in control class was 0,31 while the gain score of critical thingking in experimental class was0,58 and the gain score in control class was0,31. The effectiveness of the use models of problem based learning better in improving of understanding of concepts and critical thingking of students, it can be seen from the value obtained effect size of 0,66. In addition,based on manova test,the significance score of both understanding of concepts and critical thingking is less than 0.005. It can be concluded that there are significant effect of guided problem based learning and understanding of concepts and critical thingking of students on senior high school.Abstrak: Penelitian ini bertujuan untuk mengetahui efektivitas model pembelajaran problem based learning (PBL) terhadap pemahaman konsep dan berpikir kritis peserta didik SMA pada materi suhu dan kalor. Subjek pada penelitian ini adalah peserta didik kelas X SMA N 1 waway karya lampung timur berjumlah 70 orang peserta didik.  Metode penelitian yang dipilih yakni quasi eksperiment  dengan desain pretets-posttest control design.Data pemahaman konsep dan berpikir kritis dikumpulkan melalui instrumen tes soal essay. Data yang diperoleh kemudian di analisis menggunakan uji multivariate (MANOVA). Hasil analisis data dengan program spss 17.00 menunjukkan bahwa terdapat pengaruh penerapan model pembelajaran problem based learning terhadap pemahaman konsep dan berpikir kritis peserta didik. Nilai gain pemahaman konsep kelas eksperimen sebesar 0,51 dan nilai gain kelas kontrol sebesar 0,31 sedangkan nilai gain berpikir kritis kelas eksperimen sebesar 0,58 dan nilai gain kelas kontrol sebesar 0,31. Efektivitas penggunaan model PBL lebih efektif dalam meningkatkan pemahaman konsep dan berpikir kritis peserta didik,  ditunjukkan dengan nilai effect size pemahaman konsep sebesar 0,36 dan nilai effect size berpikir kritis sebesar 0,66. Selain itu berdasarkan hasil uji manova, baik nilai signifikansi pemahaman konsep maupun nilai signifikansi kurang dari 0,005 sehingga dapat disimpulkan bahwa terdapat pengaruh penerapan model PBL terhadap pemahamman konsep dan berpikir kritis peserta didik SMA.